2008
DOI: 10.1007/s00213-008-1340-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for modulation of facial emotional processing bias during emotional expression decoding by serotonergic and noradrenergic antidepressants: an event-related potential (ERP) study

Abstract: Citalopram and reboxetine have selective effects on the temporal course of emotional processing with evidence to suggest specific effects on emotion expression decoding of positive (happy) emotional facial stimuli as evidenced by changes in the attention-modulated N250 but not structural encoding. These findings provide physiological evidence that antidepressants may shift perceptual biases in emotional processing away from negative and towards positive stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
4

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 96 publications
(168 reference statements)
2
20
1
4
Order By: Relevance
“…However, acute SSRI administration did decrease threat recognition in previously depressed patients [50] . It was also found to enhance LPPs to sad versus neutral faces in healthy males [51] , though a subsequent study did not replicate this [52] .…”
Section: Serotonin and Facial Processingmentioning
confidence: 84%
See 1 more Smart Citation
“…However, acute SSRI administration did decrease threat recognition in previously depressed patients [50] . It was also found to enhance LPPs to sad versus neutral faces in healthy males [51] , though a subsequent study did not replicate this [52] .…”
Section: Serotonin and Facial Processingmentioning
confidence: 84%
“…As such, given the varied findings, few inferences regarding the LPP to emotive stimuli in MDD can be drawn. Direct modulations of 5-HT activity via acute SSRI administration in healthy individuals induced an enhanced LPP to sad versus neutral faces [51] and no effects [52] . The latter is consistent with our finding of an unaltered LPP following 5-HT modulations to specific emotive stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, citalopram and reboxetine increased the N250 amplitude for happy relative to sad facial expression (Kerestes et al 2009), however without an effect on behavior and mood. Application of citalopram and reboxetine over 7 days resulted in no significant changes of mood in healthy subjects (Harmer et al 2004) and had no effect on the recognition of happy facial expression, but decreased the recognition of disgusted, angry, and afraid expressions and the emotion-potentiated startle response to negative stimuli, thus pointing to an effect on the processing of negative stimuli.…”
Section: Discussionmentioning
confidence: 95%
“…Although many of these tasks involve the explicit and effortful control of emotion (McRae et al, 2010;Ochsner & Gross, 2005;Phan et al, 2005), a number of techniques have been developed recently to specifically alter the habitual deployment of attention to emotional information (Dandeneau, Baldwin, Baccus, Sakellaropoulo, & Pruessner, 2007; sants alter activity in frontal control regions; two studies reported such an effect (Fales et al, 2009;Kennedy et al, 2001), although both of these involved clinical populations, indicating that the findings may have been secondary to improved clinical status, rather than a treatment effect. An event-related potential (ERP) study has examined the effects of citalopram and reboxetine on the processing of emotional information in healthy volunteers (Kerestes et al, 2009). The high temporal acuity of ERP allowed the authors to demonstrate that both antidepressants influenced processing relatively shortly after stimulus presentation (250 msec), with the effect being found in a component of the ERP known to be sensitive to spatial attention (Eimer, Holmes, & McGlone, 2003).…”
Section: Psychological Methods Of Modulating Attention To Emotional Imentioning
confidence: 99%